Intersubband Transition Engineering in the Conduction Band of Asymmetric Coupled Ge/SiGe Quantum Wells - Luca Persichetti; Michele Montanari; Chiara Ciano; Luciana Di Gaspare; Michele Ortolani; Leonetta Baldassarre; Marvin Zoellner; Samik Mukherjee; Oussama Moutanabbir; Giovanni Capellini; Michele Virgilio; Monica De Seta (Crystals, 2020)
n-type Ge/SiGe asymmetric coupled quantum wells represent the building block of a variety of nanoscale quantum devices, including recently proposed designs for a silicon-based THz quantum cascade laser. In this paper, we combine structural and spectroscopic experiments on 20-module superstructures, each featuring two Ge wells coupled through a Ge-rich SiGe tunnel barrier, as a function of the geometry parameters of the design and the P dopant concentration. Through a comparison of THz spectroscopic data with numerical calculations of intersubband optical absorption resonances, we demonstrated that it is possible to tune, by design, the energy and the spatial overlap of quantum confined subbands in the conduction band of the heterostructures. The high structural/interface quality of the samples and the control achieved on subband hybridization are promising starting points towards a working electrically pumped light-emitting device.